A cross-sectional study of tobacco addiction among college students of Muzaffarnagar city - Muzammil, Khursheed; Singh, Sujit; Singh, Jai Veer; Dave, Sanjeev; Raghav, Santosh; Khalil, S (Indian Journal of Community Health, 2015)
Background: Tobacco consumption in any form is the second major cause of death all over the globe. The mortality because of tobacco consumption is expected to double by the year 2025. Adolescents and college going students are the most vulnerable group that develop this bad habit of tobacco consumption. Every minute approximately 9-10 people die all over due to tobacco related diseases. Keeping all these in mind the research question of this study was set as -What is the prevalence of tobacco use amongst college students? Materials & Methods: A cross sectional study was carried out for a period of 2 months in the four colleges selected by simple random sampling. Prior permission was taken from all the head of the institutions of the respective colleges. A pre-tested self-structured questionnaire was filled by all the students present at the time of visit to their colleges. At the end of the visit, students were explained about the harmful effects of tobacco use in any form. A total of 248 students were ultimately included for the purpose of the study and their responses were analyzed by using Epi info statistical package. Results: Prevalence of tobacco use in any form among study subjects has found to be 19.76%. 22.81% of the male subjects and 12.99% of the female subjects were using smokeless tobacco (SLT). Only male subjects were found to be smoker (4.09%). Gutkha was found to be used most by the boys (61.54%). Nearly 77.78% of the boys and 50.87% of the girls knew about the lung cancer and oral cancer as the consequences of tobacco smoking and chewing respectively and this finding when compared has found to be statistically significant. Majority of the boys (93.57%) and girls (93.51%) responded on the need of complete ban on the tobacco companies. Conclusions: Awareness generation through health education is one of the important aspects for the control of tobacco use. Government and general public should make joint efforts to stop the production, sale and consumption of tobacco products.